'Savoy', an Adapted Soft Red Winter Wheat Cultivar for Georgia and the Southeast Regions of the United States. Issue 1 (7th December 2017) - Johnson, Jerry W.; Chen, Z.; Buck, James W.; Buntin, G. D.; Babar, Md A.; Mason, Richard E.; Harrison, Stephen A.; Murphy, J. Paul; Ibrahim, Amir M. H.; Sutton, Russell L.; Simoneaux, Bryan E.; Bockelman, Harold E.; et al.
Abstract : Soft red winter wheat (SRWW) ( Triticum aestivum L.) is a major crop in Georgia and the southeastern region of the United States. Despite a decrease of wheat acreages in this region, about 100, 000 ha were grown to SRWW in Georgia in 2015. To capture and maximize regional market value of wheat, the new released cultivars must have high yield potential, excellent resistance levels to predominant diseases and insects, and good quality. Therefore, the major goal of the SRWW breeding program at the University of Georgia (UGA) is to develop and release SRWW cultivars adapted to the southeastern wheat region with high yield, quality, and pest resistance. 'Savoy' (Reg. No. CV‐1135, PI 676043) is a SRWW cultivar developed by the small grains breeding program at UGA in cooperation with the SUNGRAINS and released by the UGA College of Agricultural and Environmental Sciences in 2015. Savoy was subsequently licensed to CPS DYNA‐GRO Seed Company. Savoy was released because it is widely adapted to Georgia and the US Southeast. It has high grain yield, good resistance to races of leaf rust and stripe rust predominant in Georgia and the Southeast. Savoy possesses the H13 gene that confers resistance to predominant biotypes of Hessian fly in Georgia and the Southeast. It has good resistance to powdery mildew and Soil‐borne wheat mosaic virus . Savoy is moderately susceptible to Fusarium head blight, or scab. It also has high grain volume weight and acceptable SRWW milling and baking quality.